Kepimimpinan KH. Muhammad Sanusi Dalam Membangun Karakter Disiplin Santri - Muhammad Jalal Assayuti (Oasis : Jurnal Ilmiah Kajian Islam, 2024)
This study aims to analyze the leadership of KH. Muhammad Sanusi in building the disciplinary character of students in pesantren, focusing on the application of Islamic values and exemplary behaviors that influence student conduct. This research employs a qualitative method with a descriptive approach, utilizing observations, interviews, and documentation studies with students, pesantren administrators, and other related parties. The results show that the charismatic and authoritative leadership of KH. Muhammad Sanusi effectively instilled a strong sense of discipline in students. He implemented discipline through direct example, firm rules regarding worship, dress code, and daily behavior. Although KH. Muhammad Sanusi has passed away, the values he taught remain alive and continue to guide students in their daily lives within the pesantren. Thus, this study highlights that consistent, charismatic leadership can have a lasting impact in shaping the disciplinary character of students